Hubungan Tingkat Pengetahuan, Sikap dan Karakteristik Masyarakat dengan Pencegahan Demam Berdarah Dengue di Puskesmas Bola - Maria Lidvina; Lewi Jutomo; Indriati A. Tedju HInga (Yayasan Literasi Sains Indonesia, 2023)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus through the bite of the Aedes aegypti mosquito which still affects the world's population today. DHF cases at the Bola Health Center are still very high so it is necessary to pay attention so that preventive measures can be taken. This study aims to analyze the relationship between the level of knowledge, attitudes and characteristics (age, income, employment, education) of the community and the prevention of dengue hemorrhagic fever in the Working Area of the Bola Health Center in 2022. The type of research used was an analytic observational study with a cross-sectional design. . This research was conducted in the working area of the Bola Health Center with a sample of 97 families. The data analysis used was univariate and bivariate analysis with the chi square statistical test . The results of this study indicate that there is a relationship between knowledge (p=0.011), attitude (p=0.040), education (p=0.044) and prevention of dengue hemorrhagic fever in the working area of the Bola Health Center. Meanwhile, those that were not related to the prevention of dengue hemorrhagic fever (DHF) in the working area of the Bola Health Center were age (p=0.711), income (p=0.062), occupation (p=0.544). It is hoped that the community will be more active in finding out about DHF and things that must be considered in preventing in the surrounding environment and taking real action by carrying out prevention efforts recommended by health workers.